The Role of Transformational Leadership in Enhancing the Sustainable Performance of Organizations: An Exploratory Study of the Opinions of a Sample of Educational Leaders at the University of Qadisiya - Nadia Kazem Awad Hussein; Majid Fahem Jaafar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research aims to determine the level of sustainable organizational performance from opinion of view of some learning leaders, and to know the level of organizational innovation from opinion of view of some learning leaders, and to reveal the level of organizational flexibility according to the opinion of some educational leaders, and to indicate the level of organizational capacity among individuals The university of the research sample, and determine the level of practices of learning leaders Research sample for transformational leadership behaviors, and the research also aims to test the correlation between transformational leadership and sustainable organizational performance, and test the impact relationship between transformational leadership and sustainable organizational performance. The research was applied at the University of Qadisiyah to a sample of administrative leaders at this university.